Determination of Atrazine, Simazine, Alachlor, and Metolachlor in Surface Water Using Dispersive Pipette Extraction and Gas Chromatography–Mass Spectrometry. (4th March 2018) - Guan, Sharon Hongxia; Huang, Michelle Wenlin; Li, Xiaoping; Cai, Qingsong
ABSTRACT: Four commonly found pesticides (alachlor, atrazine, metolachlor, and simazine) in surface water were determined using dispersive pipette extraction followed by gas chromatography–mass spectrometry. The rapid mixing and equilibrium between the dispersive pipette extraction adsorbent and water sample resulted in fast and efficient extraction. Using only 5 mL of water sample, the estimated time consumption for extraction of each sample was less than 5 min. Method validation was performed to evaluate accuracy, precision, linearity, the limits of detection, and the limits of quantitation. Average recovery of above 90% was obtained with relative standard deviations below 10%, which indicated good accuracy and precision of the dispersive pipette extraction method. Coefficients of determination were all above 0.9901 and showed good linearity. For the four pesticides studied using the current method, the limits of detection ranged from 7 to 40 ng L −1, and limits of quantitation were from 20 to 130 ng L −1 . Method validation results supported the application of the current method for drinking water safety monitoring per National Primary Drinking Water Regulations established by the US Environmental Protection Agency. Water samples from Lake Lanier and Stone Mountain Lake (Georgia, USS) were analyzed with this method as a preliminary work for a larger scale drinking water quality study in the future. Trace amounts of simazine and atrazine were found in lake water samples, but both were below the regulation levels of the US Environmental Protection Agency.